A brief review of literature on issues and challenges of business continuity management for small and medium-sized enterprises in developing countries. (28th December 2022) - Musumali, Mbaulo; Qutieshat, Abubaker
The paper aims to review and critically analyse existing literature on issues and challenges hindering business continuity management from being widely implemented by small and medium-sized enterprises (SMEs) in developing countries. Electronic search was conducted in Google Scholar, Springer, and ScienceDirect databases using selected keywords to identify papers published in English from 2012-2020. Evaluation of fit for review conducted to shortlist appropriate articles to use. Findings established that despite gradual increase of publications on business continuity in SMEs, there is still inadequate research interest from body of research evidenced by few researched papers published on this topic. It was also found that SMEs in developing countries were characterised by low implementation of business continuity management due to low prioritisation, resource limitation, knowledge, and capacity. This is the only identified recent review of literature on business continuity management for SMEs with wider context covering developing countries in general and conducted within last nine years.